The utility of HepaRG cells for bioenergetic investigation and detection of drug-induced mitochondrial toxicity. (December 2018) - Kamalian, Laleh; Douglas, Oisin; Jolly, Carol E.; Snoeys, Jan; Simic, Damir; Monshouwer, Mario; Williams, Dominic P.; Kevin Park, B.; Chadwick, Amy E.
Abstract: The importance of mitochondrial toxicity in drug-induced liver injury is well established. The bioenergetic phenotype of the HepaRG cell line was defined in order to assess their suitability as a model of mitochondrial hepatotoxicity. Bioenergetic phenotyping categorised the HepaRG cells as less metabolically active when measured beside the more energetic HepG2 cells. However, inhibition of mitochondrial ATP synthase induced an increase in glycolytic activity of both HepaRG and HepG2 cells suggesting an active Crabtree Effect in both cell lines. The suitability of HepaRG cells for the acute metabolic modification assay as a screen for mitotoxicity was confirmed using a panel of compounds, including both positive and negative mitotoxic compounds. Seahorse respirometry studies demonstrated that a statistically significant decrease in spare respiratory capacity is the first indication of mitochondrial dysfunction. Furthermore, based upon comparing changes in respiratory parameters to those of the positive controls, rotenone and carbonyl cyanide m -chlorophenyl hydrazone, compounds were categorised into two mechanistic groups; inhibitors or uncouplers of the electron transport chain. Overall, the findings from this study have demonstrated that HepaRG cells, despite having different resting bioenergetic phenotype to HepG2 cells are a suitable model to detect drug-induced mitochondrial toxicity with similar detection rates to HepG2 cells. Highlights: HepaRG cells are studied from a bioenergetic and mito-toxicity point of view. They have more OXPHOS mediated respiration but less glycolysis than HepG2 cells. Like HepG2s they can switch to glycolysis acutely, and are fit for glu/gal assay. They offer similar level of detection to HepG2s in glu/gal mitotoxicity screen. A seahorse based strategy is introduced to mechanistically categorise compounds.